Implementasi Model Pembelajaran Problem Based Learning Sebagai Keterampilan Menulis Deskripsi Siswa Pada Abad 21 - Nursaadah, Adah; Rodiyana, Roni (Papanda Publisher, 2023)
The problem-based learning model as a student description writing skill in the 21st Century requires students to keep up with the times in the 4.0 revolution era. This study aims to determine 1). Problem Based Learning learning model as a student description writing skills in the 21st Century 2). How to apply the Problem Based Learning learning model as a student description writing skill in the 21st Century. This research is a systematic literature study, the research steps are to find articles that match two keywords, meet the inclusion inclusion criteria, pass the quality assessment consisting of an assessment of research questions, methodology, and research results. The results showed that by implementing the writing process in learning, the learning steps also used the writing process, including prewriting, drafting, revising, editing, and publishing. Learning Indonesian about writing descriptive texts for fictional characters, students learn new things, open students' knowledge that writing is not just a product, but writing also has processes including prewriting (prewriting), writing (drafting), revision (revising), editing ( editing), and publication (publishing).